monyod
Answered

Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

6x+3x-(x-10)=20x help... step by step.


Sagot :

6x+3x-(x-10)=20x
Distribute -1 to (x-10)
6x+3x-x-(-10)=20x
9x-x-(-10)=20x
8x-(-10)=20x
Subtract 8x to 20x
-10=12x
Divide 12x to -10
-1.2=x
in equations we always want to do the same thing to both sides so the equation stays equal

in an equation with one unknown (x) we try to get the unknown on one side

so -(x-10)
this means that you multiply everything in the equation by -1 or in other words you make everything in the parenthasees the opposite sign of what it is so

6x+3x-x+10=20x
add like terms
8x+10=20x
subtract 8x from boths sides
10=12x
divide both sides by 12
10/12=x=5/6